The Sufistic Values in the Tolokin Tujuh Tradition in the Village of Rambah Samo Barat, Rokan Hulu - Nanda, Heru; Wilaela, Wilaela; Abduh, M. Arrafie (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2024)
This article contains about the procession and sufistic values in the Tolokin Seven ritual in the community which is still going on until now. The purpose of the tradition is to pray for people who have died in the community of Desa Rambah Samo Barat, Rokan Hulu. Data collection in this descriptive qualitative research is done through observation, interviews, and documentation. Informants numbered seven people, consisting of mursyid, traditional figures, religious figures, community figures, culturalists and adult male and female community members. The results of the research explain the traditional seven-day tolokin procession , which begins with the community going to the destination grave after the dawn prayer, and sitting in a circle around the grave. They read istighfar , silsilah Yasin, surah al-Fatihah, surah al- Insyrah , surah at- Takatsur , Surah Yasin, prayer tolokin seven , surah al-Ikhlas, surah al- Falaq , surah an-Nas, tahlil, prayer, salam- shake hands and end with the members of the temple giving alms in the form of food and drink. The sufistic values contained in the seven tolokin tradition are the values of asceticism and repentance, khauf and king', patience and gratitude, sincerity, trust, reflection, and rida. The tradition of tolokin seven is maintained and practiced by the people of West Samo Rambah Village because it is believed to be in accordance with religious teachings or not contrary to Sharia and teaches that each individual will be held accountable for all actions.Abstrak: Artikel ini mengkaji tentang prosesi dan nilai-nilai sufistik dalam ritual tolokin tujuh dalam masyarakat yang masih berlangsung hingga kini. Tujuan dari tradisi tersebut untuk mendoakan orang yang telah meninggal dunia di dalam masyarakat Desa Rambah Samo Barat, Rokan Hulu. Pengumpulan data dalam penelitian kualitatif deskriptif ini dilakukan melalui observasi, wawancara, dan dokumentasi. Informan berjumlah tujuh orang, terdiri dari mursyid, tokoh adat, tokoh agama, tokoh masyarakat, budayawan dan anggota masyarakat laki-laki dan perempuan dewasa. Hasil penelitian menjelaskan tentang prosesi tradisi tolokin tujuh diawali dari masyarakat mendatangi kuburan yang dituju setelah salat subuh, dan duduk melingkar mengelilingi kuburan tersebut. Mereka membaca istighfar, silsilah Yasin, surah al-Fatihah, surah al-Insyirah, surah at-Takatsur, Surah Yasin, doa tolokin tujuh, surah al-Ikhlas, surah al-Falaq, surah an-Nas, tahlil, doa, bersalam-salaman dan diakhiri pemberian sedekah oleh ahli bait, berupa makanan dan minuman. Nilai-nilai sufistik yang terkandung dalam tradisi tolokin tujuh adalah nilai zuhud dan tobat, khauf dan raja’, sabar dan syukur, ikhlas, tawakal, muhasabah, dan rida. Tradisi tolokin tujuh tetap dipertahankan dan dipraktikkan oleh masyarakat Desa Rambah Samo Barat karena diyakini sesuai dengan ajaran agama atau tidak bertentangan dengan syariat dan memberikan pengajaran bahwa setiap individu akan dimintai pertanggungjawaban atas segala perbuatan.